The Compact with the Charter and Laws of the Colony of New Plymouth 102 (William Brigham ed., 1836) (enacted 1656) (Apr. 1 through Nov. 30) - (:unkn) unknown (My University, 1657)
Required the militia of every township to bring arms during Sunday church services. Violators fined twelve pence for every default.
Keywords: REQUIRED POSSESSION